THE DECLINE OF BRAZILIAN INDUSTRY: AN ANALYSIS THROUGH SELECTED INDICATORS (2000-2019) - de Oliveira, Luardo Sanches Silva; Ribeiro, Luana da Silva; Nascimento, Julio Cesar (Seven Editora, 2026)
This work tries to understand the decline of the Brazilian industry in the period covering the years 2000 to 2019, based on selected indicators. For this, it starts from the orthodox and heter- odox definitions of the phenomenon of de-industrialization; the indicators are presented based on a vast literature; and a brief context of the Brazilian economy in the years prior to the period under review. Subsequently, data and indicators of the Brazilian economy in the period are presented in order to observe its behavior. Next, the Brazilian political and economic situation will be considered in order to try to explain the reason for the behavior of the data. Finally, the conclusions will be presented.